Inflammation and itching in patients suffering from atopic dermatitis and psoriasis. Assessment of the expression of neurotrophins аnd neuropeptides - V. A. Smolyannikova; A. A. Kubanova; V. V. Chikin; A. E. Karamova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Goal. To assess the expression of neurotrophin, a nerve growth factor, amphiregulin, an epidermal growth factor, semaphorin 3A, a nerve repulsion factor, and PGP9.5 protein, a nerve fiber marker, in the skin of patients suffering from atopic dermatitis and psoriasis. Materials and methods. The study involved 30 patients suffering from atopic dermatitis and 30 patients suffering from psoriasis vulgaris. The disease severity was assessed by SCORAD and PASI. The extent of itching was assessed by the visual analogue scale. The expression of amphiregulin, semaphorin 3A (a nerve growth factor) and PGP9.5 protein (a nerve fiber marker) in the skin of patients was assessed by the indirect immunofluorescence method. Quantitative parameters of their expression were assessed by using the basic pack of the Olympus Fluoview software, Ver. 1.7b. Results. Increased epidermal innervation was revealed in the patients suffering from atopic dermatitis and psoriasis, which demonstrates an increased skin production of anti-inflammatory neuropeptides and reduced itching sensitivity threshold. A positive correlation between the itching extent and skin expression of neurotrophin (a nerve growth factor) was revealed in the patients with atopic dermatitis. In patients with severe psoriasis, an increased skin expression of amphiregulin, an epidermal growth factor, was discovered. Conclusion. These data demonstrate a pathogenic value of neurotrophin, a nerve growth factor, for the development of itching in patients with atopic dermatitis and amphiregulin in case of psoriasis vulgaris.